Impaired diffusion tensor imaging findings in the corpus callosum and cingulum may underlie impaired learning and memory abilities in systemic lupus erythematosus. (October 2016) - Shapira-Lichter, I; Weinstein, M; Lustgarten, N; Ash, E; Litinsky, I; Aloush, V; Anouk, M; Caspi, D; Hendler, T; Paran, D
Background: Memory impairment is prevalent in systemic lupus erythematosus (SLE); however, its pathogenesis is unknown. In a previous functional magnetic resonance imaging (fMRI) study we demonstrated altered brain activity dynamics and less brain deactivation in patients with SLE as compared with healthy controls, when performing a learning and memory task. Our findings localized this impairment to the default mode network (DMN), and particularly to its anterior medial prefrontal cortex node. In addition, altered networking of the hippocampal subsystem of the DMN was seen in patients with SLE when performing this task, as well as atrophy of the left hippocampus. The present study aimed to search for a structural substrate for the altered recruitment pattern observed in fMRI studies using diffusion tensor imaging (DTI). Patients and methods: Using DTI, we characterized brain diffusivity in 10 patients with SLE and nine healthy controls. Two tracts associated with the DMN were reconstructed: the corpus callosum (CC) and the cingulum bundle. The CC was segmented according to the Witelson segmentation scheme and the cingulum was segmented into superior and descending bundles. Results: A significant increase in mean diffusivity (MD) was seen in patients with SLE without neuropsychiatric SLE (NPSLE) as compared with healthy controls in all five segments of the CC (segment 1: p = 0.043; segment 2: p = 0.005; segment 3: p = 0.003; segment 4: p = 0.012; segment 5: p = 0.023) as well as in the descending portion of the left cingulum bundle ( p = 0.026). Conclusions: Increased MD values in the CC and the left cingulum may indicate impaired organization/reduced integrity of these tracts, which may underlie the abnormal pattern of brain activity recruitment of the DMN observed during a verbal learning and memory task. Taking into account the central role of the left hippocampus in verbal memory, the abnormal integrity of the left cingulum may contribute to the reduced performance of patients with SLE on verbal memory tasks.